EMPIRICAL RESEARCH OF COMMUNICATIVE DISCOURSE OF CHILDREN’S COMPUTER CULTURE - Juodaitytė, Audronė; Šaparnytė, Erika (Acta Paedagogica Vilnensia, 2008)
The paper deals with a communicative discourse of children’s computer culture. A theoretical approach to a research on a communicative discourse of children’s computer culture in the context of social reality construction is presented highlighting the aspects of communication freedom, communication mobility, communication relations, changes of roles, significance (positive and negative) of communication. The paper reveals how one of modern methodological approaches, a social reality construction theory (Berger, Luckman, 1999). The procedure of carrying out this kind of research and the characteristics of data analysis have been described. Methodological approaches based on phenomenology, postmodern discourse, theory of social reality construction and methodology of qualitative research of a carried out qualitative research are presented. Children’s understanding of a communicative discourse of computer culture has been described using the method of an essay; research organisation and qualitative data analysis procedures based on I. E. Seidman’s strategy, inductive logics, content analysis and the method of continuous comparison are presented. Referring to the peculiarities of children’s virtual communication the authors have described children’s communicative discourse of computer culture in detali and have identified that children construct a communicative discourse of computer culture recognizing a computer as a communication technology. They have showed the content of this discourse as well as its socio-educational meaning highlighting full-fledgedness of children’s computer culture and its significance for the development of general communicative culture of society. Children’s computer culture has been advocated as a modern socio-educational phenomenon as well as a children’s life practice of worldview significance for both the educators and the parents. It is important to understand and tolerate in order to develop children’s as creators of communicative culture competences.